Capabilities approach and professional ethics in university education for democracy: the case of business and humanities careers at a private university in Mexico - López-Calva, Juan Martín; Méndez Escarza, Claudia Rebeca (IE Revista de Investigación Educativa de la REDIECH, 2021)
This research is based on the theoretical contribution of the capabilities approach of American philosopher Martha Nussbaum as a source of ethical criteria of university education that guide professional training towards the construction of authentically human societies and her distinction between what she calls education for profit and education for democracy. Based on these features, a semi-structured interview guide was constructed and later applied to a sample of eight academics from a private university, who are in charge of directing undergraduate programs in the areas of Business and Humanities, in order to learn how do they conceive and are putting into practice the training of future professionals in their respective disciplines. Some differences were found in the comparison between both areas, but the results generally show an orientation towards education for democracy in the careers of both disciplinary fields with a greater emphasis and clarity in those of Humanities, which may be due either to the understanding and adherence to the ideology and mission of the university where the study was carried out or the use of a learned institutional discourse.